Epistolary Writing: From Divine Gift to Literary Creation - Sellami, Abdeddayem; Alsaied, Mohamad Abdullah (Journal of Ecohumanism, 2025)
In the movement of human thought, there are two dimensions that affect and influence each other: one reflects the features of mental function, which deals with material reality in analysis, conclusions, and impact. The second function is symbolic, by which a person reaches his imagination, goes beyond his senses, and opens up to everything that is amazing and extraordinary. No matter how much we achieve in scientific progress, a symbolic horizon is still necessary in order to overcome the conditions of doubt, suspicion, and boredom, and achieve a balance between scientific knowledge and imagination, restriction and absolute, and mundane and sacred. Within a host argument, the symbol is renewed and imagination is enriched.There are many manifestations of this meeting between the mundane and the religious in Arabic literature, and this is the relationship between literature and the sacred that stands out to us. It is therefore evident that epistolary literature, being an ancient literary genre, is similar to the sacred in that it quotes the sacred as the formative conditions of its sender and message. The research used the comparative approach and the descriptive analytical approach to reveal the manifestations of this similarity, its limitations, and the extent of its ability to enrich the literature of epistolary. It has been concluded from all this that when the epistolary was opened to the sacred world, it recalled most of its religious loads and gave it the literary message until it was raised, among the ancient epistolaries, to the rank of the sacred message in form and content.